Chronic Port Site discharging sinus following Laparoscopic Cholecystectomy: An experience of 5 years at a tertiary health care centre - Faridi, Shahbaz Habib; Siddiqui, Bushra; Harris, Hasan; Hussain, Danish; Mittal, Saurabh (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Laparoscopy has replaced the open technique in the majority of cholecystectomy surgeries. However laparoscopic surgeries are associated with some of its own set of complications amongst which one of the most bothersome is chronic port site infection. It adds to the morbidity of the patient and also undermines the benefit of laparoscopic surgery. Infection with rapidly growing atypical mycobacteria having multidrug resistance is frequently encountered in many of these patients. This study focuses on the clinical diagnosis, management, and prevention of this problem at a tertiary centre. Material and methods: This study has been done in 40 patients who suffered from chronic port site infection over a period of 5 years in a tertiary care centre. Result: Majority of the patients presented 4 weeks after laparoscopic surgery with a discharging sinus. Altogether 19 patients (48%) completely responded with prolonged fluoroquinolone for 6- 8 weeks without any surgical intervention. Anti-tubercular therapy was given in 15 patients (37%) and surgical debridement followed by fluoroquinolone and antitubercular therapy for 6-9 months was given in 6 patients (15%). Conclusion: Chronic port site infection is a rare preventable complication if appropriate measures are taken preoperatively, intraoperatively and postoperatively. It can often be treated nonsurgically, with early identification and appropriate management. It can be best avoided by proper sterilization techniques of the laparoscopic instruments with appropriate sterilizing agent for appropriate time. International Journal of Human and Health Sciences Supplementary Issue 02: 2023 Page: S95-S105